HBEC 2203: Early Childhood Education Curriculum - study guide - Badzis, Mastura (Open University Malaysai (OUM), 2011)
This course is designed to enhance student’s understanding of curriculum in early childhood education. The course content will revolve around exploration and reflection upon curriculum models/approaches in early childhood education, curriculum decision making, curriculum practices across various countries/programmes, strategic learning and teaching processes in six (6) of early childhood curriculum areas. Quality environment such as arrangement of indoor/outdoor spaces as well as locating, planning, implementing and evaluating creative learning activities using a variety of methods and materials will also be discussed.